2012
DOI: 10.1016/j.msea.2011.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural design for mechanical and electrical properties of spark plasma sintered Al2O3–SiC nanocomposites

Abstract: a b s t r a c tAl 2 O 3 -17 vol.% SiC nanocomposites were prepared by powder mixture of submicrosized ␣-Al 2 O 3 , nanosized ␥-Al 2 O 3 and different nanosized ␤-SiC. Materials were sintered by spark plasma sintering (SPS) technique at two temperatures (1400-1550• C) and their electrical conductivity and mechanical properties were investigated. High-density composites have been achieved even at the lowest sintering temperatures and the microstructure characterization shows SiC particles located both within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Only a few research papers on the functional properties (thermal and electrical conductivity) of Al 2 O 3 -SiC nanocomposites have been published so far [ 121 , 122 ], despite the fact that thermal conductivity is an important parameter in many applications of alumina-based ceramics, including high temperature structural components, refractories for glass and metal production industries, gas radiant burners, wear parts, and cutting tools. In all these applications, the thermal conductivity has to be as high as possible, in order to reduce thermal shock-related failure of the components.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…Only a few research papers on the functional properties (thermal and electrical conductivity) of Al 2 O 3 -SiC nanocomposites have been published so far [ 121 , 122 ], despite the fact that thermal conductivity is an important parameter in many applications of alumina-based ceramics, including high temperature structural components, refractories for glass and metal production industries, gas radiant burners, wear parts, and cutting tools. In all these applications, the thermal conductivity has to be as high as possible, in order to reduce thermal shock-related failure of the components.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…[5][6][7] It seems that to dominate the intrinsic brittleness of alumina, composition of new materials is necessary. The Al 2 O 3 -17 vol.% SiC nanocomposites were prepared by Borella et al 19 using submicrometer Al 2 O 3 and SiC nanoparticles. There are several materials which have been used as the second phase particles to enhance the properties of Al 2 O 3 matrixes including SiC, 8 ZrO 2 , 9 TiN/TiC/TiO 2 , 10,11 BN, 12 and Y 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, they suggested that the residual stresses around the SiC particles in these composites led to increasing the strength and toughness of samples by crack deflection and micro-crack mechanisms. The Al 2 O 3 -17 vol.% SiC nanocomposites were prepared by Borella et al 19 using submicrometer Al 2 O 3 and SiC nanoparticles. The specimens were sintered by SPS process at temperatures of 1400 • C and 1550 • C. In this work, they found that the lower sintering temperature was a good choice for achieving the high-density specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Al 2 O 3 -reinforced with nano-sized particles, such as TiB 2 , SiC, TiC, WC, NbC and others, represent a new class of materials with improved mechanical properties, especially the fracture toughness, hardness and wear resistance [1][2][3][4][5][6][7][8][9]. This new class of materials can be an interesting alternative for the production of cutting tools in order to improve cutting speed and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the sinterability of these materials and obtain mechanical and wear properties with a higher quality than the current properties, an interesting technique is the Spark plasma sintering (SPS), also known as field-assisted sintering technique (FAST). This technique is based on applying an on-off dc (direct current) electric pulse under uniaxial pressure that it is used for rapid fabrication of nanocrystalline ceramics [3,4,5]. This technique can work at heating rates on the order of hundreds of degrees per minute, reaching high temperatures in very short time, providing dense materials after cycles of heating/cooling of only a few minutes.…”
Section: Introductionmentioning
confidence: 99%